The Role of Knowledge in Moderating Compliance Behavior of Private Taxpayers in Yogyakarta - budi setyanta; Mohammad Najmudin; Eni Andari; Faniko Yudha Apriadi (Cita konsultindo, 2023)
The primary objective of this research is to forecast how tax knowledge impacts the compliance behavior of individual taxpayers. The study utilizes the Theory of Perceived Behavior, incorporating tax sanctions as a variable. The participants in the study are taxpayers who fulfill their tax obligations. The PLS-SEM test is employed to identify the influence of independent variables on tax compliance. The findings reveal that tax knowledge does not moderate this study's independent variables (attitudes, subjective norms, perceived behavioral control, and tax sanctions). However, further investigation is necessary to explore whether tax liability moderates tax compliance. The tax liability would help ascertain the role of tax liability in influencing tax compliance behavior